The Influence of Discovery Learning toward the Science Conceptual Understanding and Perceptions of the Dangerous of Smoking for Primary School Learners - Fahmiyati, Masitoh Arif; Sunarso, Ali; Lisdiana, Lisdiana (Educational Management, 2021)
This research aims to find out the discovery learning model toward the science conceptual understanding and perceptions of the danger of smoking for learners. This is experimental research with one group pre-test post-test design. The population consisted of the whole fifth graders in the academic year 2019/2020, from Ki Hajar Dewantoro cluster, Mertoyudan Magelang. The sample consisted of the fifth graders of Parikan Public Primary School, Kalinegoro Public Primary School, and Soroyudan Public Primary School. The applied data collection techniques were a test and a questionnaire. The applied instrument consisted of an essay and a questionnaire sheet. The obtained data were then analyzed by using N-Gain, descriptive statistics, and correlation tests. Based on the findings, it could be concluded that: (1) there were improvements of science conceptual understanding after being taught by the discovery learning model, (2) the perceptions upon the danger of smoking tended to be extremely excellent after being taught by the discovery learning model, and (3) the existence of positive and significant correlations between the science conceptual understanding and the perceptions of the danger of smoking for learners.